Filling Machine Panel Retrofit into Arduino Nano-Based Digital System at CV Sarana Engineering - Surya Wijaya, Wildan; Ilham, Aditya; Abdul Jumali, Muhamad; Rochman, Sagita; Solikin, Akhmad; Nafisah, Nihayatun (BEST, 2025)
The control panel on the filling machine is an important component in the industrial automation system that functions to regulate the work sensors, actuators, and time-based control devices. This research begins with the emergence of ideas or needs to develop a system or solve a problem, which is then followed by problem identification and literature study to strengthen the theoretical basis. This study aims to redesign the filling machine control panel using a modular approach based on the Arduino Nano microcontroller. By replacing analog components with digital ones such as relay channels, LCDs, and modular PCBs, a cost efficiency analysis was carried out between the old and new systems. Testing was carried out by evaluating the response time, stability, and actuator coordination of the control panel, as well as conducting an economic analysis that included cost reduction and Return on Investment (ROI) calculations. These indicators were compared between the new and old panels to assess improvements in both technical performance and economic efficiency. The results showed that the new panel improved response speed, stability, and actuator coordination, while achieving cost savings of up to 80% compared to the conventional panel.The Return on Investment (ROI) analysis indicated an ROI of 405%, which demonstrates a significant economic advantage as the initial investment can be recovered multiple times over. This result highlights that the redesigned system is not only technically superior but also cost-effective and flexible, making it highly suitable for small to medium-scale industries. This system is also more modular, easy to program, and supports digital interface integration, making it a feasible and sustainable automation solution